2018
DOI: 10.5377/rct.v0i23.6859
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la actividad farmacológica del extracto de Bauhinia monandra en el Municipio de la Villa de San Francisco, Departamento de Francisco Morazán

Abstract: El análisis de la actividad farmacológica de los extractos acuosos, metanólicos y etéreos del taxón vegetal Bauhinia monandra Fabaceae, comúnmente conocida como “casco de vaca”, tiene el objetivo de demostrar científicamente la actividad bactericida de la planta, para poder brindar un aporte científico de la misma, contribuyendo al adecuado uso terapéutico y evaluar su futura comercialización. El material vegetal fue obtenido en el Municipio de la Villa de San Francisco, Francisco Morazán, a través de un muest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another empirically well-known species is Eryngium heterophyllum Engel, also called "toad grass", which is considered useful for the treatment of diabetes, arthritis, and hypercholesterolemia, among other diseases. The commonly recommended form of use is to prepare the aerial part of the plant in its natural state, pulverized and boiled in water, and the infusion is supplied according to the condition [4,8]. It has also been reported to be useful for the control of gallstones [23].…”
Section: Traditional Usesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another empirically well-known species is Eryngium heterophyllum Engel, also called "toad grass", which is considered useful for the treatment of diabetes, arthritis, and hypercholesterolemia, among other diseases. The commonly recommended form of use is to prepare the aerial part of the plant in its natural state, pulverized and boiled in water, and the infusion is supplied according to the condition [4,8]. It has also been reported to be useful for the control of gallstones [23].…”
Section: Traditional Usesmentioning
confidence: 99%
“…In the same way, García-Gómez et al (2019) [65], in a 1-month clinical study, showed that combined treatment of E. heterophyllum and Amphipterygium adstringens with proven hypocholesterolemic activity tested in rats, reduced triglyceride levels by an average of 20%. On the other hand, Carreón-Sánchez et al (2013) [4] showed that the ethanolic extract of E. heterophyllum, after being administered to mice by oral gavage in a single dose of 100 mg/kg of weight in a volume of 0.2 mL/30 g, had no hypoglycemic effect or acute or chronic anti-inflammatory effect; nor did it cause visible toxic effects in the acute poisoning model in mice.…”
Section: Eryngium Heterophyllummentioning
confidence: 99%
See 1 more Smart Citation